KARAKTERISTIK SURIMI YANG DIBUAT DARI HASIL PENCUCIAN DAGING IKAN CAKALANG (Katsuwonus pelamis L) DENGAN AIR DINGIN (Â± 4ÂºC) - Saliada, Farnis; Onibala, Hens; Taher, Nurmeilita; Harikedua, Silvana Dinaintang; Pandey, Engel Victor (Sam Ratulangi University, 2017)
This research intended to study the effect of washing period of skipjack (Katsuwonus pelamis L) meat with cold water to the chemical and physical properties of surimi. The functional properties of surimi was tested either byÂ physical or chemical analysis. In this study we measured folding test, texture and fat content. A complete randomized design were designated for this study with washing period as a treatment ( 0, 1, 2, 3, or 4 min). The average value of folding test were 2.2, 2.6, 3.0, 3.8 and 4.6, respectively. There is an increment of folding test value as the washing period increased. The average value of the texture analysis were 3.0, 3.8, 4.4, 5.1 and 5.9. Likewise, the longer the washing time, the firmer the texture. However, as the washing period increased, the fat content of surimi tend to decrease.